A combined low‐pressure hydrogen peroxide evaporation plus hydrogen plasma treatment method for sterilization − Part 2: An intercomparison study of different biological systems. Issue 8 (26th December 2016) - Lackmann, Jan‐Wilm; Fiebrandt, Marcel; Raguse, Marina; Kartaschew, Konstantin; Havenith, Martina; Bandow, Julia E.; Moeller, Ralf; Awakowicz, Peter; Stapelmann, Katharina
Abstract : Low‐pressure plasmas are a promising alternative to modern sterilization processes. As plasma is a surface process, multilayered stacks of spores are a crucial challenge to overcome. Here, a combined process of condensed hydrogen peroxide and hydrogen plasma is analyzed for its efficacy against various spore concentrations showing a clear increase in efficacy using a combined process compared to the two steps used separately. Besides spores, protein contaminations are a major issue in clinics and the combined process is investigated for protein removal efficiency using the well‐established BSA model. Furthermore, RNase A serves as a difficult‐to‐inactivate protein model to investigate protein inactivation efficiency. Finally, inactivation mechanisms of RNase A with a special focus on sulfur‐based modifications are investigated using Raman spectroscopy. Abstract : Plasmas as surface processes are challenged by multilayered stacks of spores. A combined process of condensed hydrogen peroxide and hydrogen plasma is analyzed for its efficacy against and proteins showing a clear superiority compared to plasma‐only process. Furthermore, the combined process is investigated for protein removal and inactivation efficacy and inactivation mechanisms are investigated.